IMPACT OF SMOKING ON OUTCOMES AFTER PERCUTANEOUS CORONARY INTERVENTION (Journal of Medical & Health Sciences Review, 2025)
Introduction: Smoking is known to be a risk factor for cardiovascular diseases, including those that require percutaneous coronary intervention (PCI). The aim of this paper was to evaluate the impact of smoking on clinical outcomes of PCI, including mortality, complications, and survival.Objective: The article attempts to assess the effects of smoking on the clinical outcomes of post-PCI, such as recurrent myocardial infarction (MI), arrhythmias, revascularization needs, and survival.Materials and Methods: The research was a retrospective cohort study conducted at Department of Cardiology, Ch Pervaiz Elahi Institute of Cardiology, Multan, between February, 2025 and July, 2025. The patients were categorised as current smokers, former smokers, and non- smokers, and the clinical outcomes were compared.Results: Current smokers had a significantly higher recurrent MI, arrhythmia, and MACE. The non-smokers had the highest chances of surviving in the long term. Smoking was also associated with worse outcomes despite other risk factors having been considered.Conclusion: Smoking significantly worsens the outcome of PCI, and cessation has a role in improving the post-procedural prognosis.